The Effect of Digital Learning on Student Mathematics Achievement at Junior High School - Rahmadani, Farah Putri; Johar, Rahmah; Hidayat, Mukhlis (Universitas Papua, 2023)
During the industrial revolution 4.0, technology to help students learn mathematics was developed, one of which is a digital learning platform. The presence of startup companies that market digital learning platforms aims to improve students’ achievement. However, some people think the digital learning platforms at this time are considered as a means to seek profit only because currently, the number of digital learning platforms is growing rapidly and vastly. This study aimed to determine the effect of digital learning on student mathematics achievement and the correlation between the level of use of digital learning platforms and mathematics achievement. This study used a quantitative approach with a correlation research type. The population in this study was all students of grade 9 of one junior high school in Banda Aceh, Indonesia, total of 155 students. The instruments were a digital learning platforms usage level questionnaire and student mathematics achievement score. The data analysis used in this study was the chi-squared test and contingency coefficient. The results of the analysis obtained from this study are there is an effect of digital learning on students' mathematics achievement, and the correlation between level of use of digital learning platforms and mathematics achievement was very high. This study is expected to provide information as a basis for consideration, support, and guidance for students to utilize learning resources on digital learning platforms that have been widely available so that improve mathematics achievement.